A Perspective Review of Security Issues in IoT with Cloud Environment - Shakya, Subarna (Journal of ISMAC, 2022)
The Internet of Things (IoT) is a paradigm that is rapidly growing in all important fields of telecommunications. Cloud computing is a computing technique that provides a large amount of storage space for data enhancement. The integration of IoT and cloud computing expands storage space for a larger number of users while maintaining the data communication between the different end users. By combining the computing and communication paradigms, this integration produces an efficient result. The main disadvantage is security, which is the most important issue nowadays. This review paper examines the various security issues and potential solutions in the integration of IoT and cloud computing. This review work finalizes light weight cryptography such as block cypher and authenticate cypher approaches, which helps to improve data storage for efficient communication between multi users.
Keywords: Security issues; cryptography techniques; IoT; cloud computing; data processing